202k views
0 votes
Divide 26x^4 - 13x^3 - 74x^2 - 46x - 24 by 2x^2 - 3x -5 and verify the result by division algorithm

User Sameen
by
5.5k points

1 Answer

4 votes

Answer:

Explanation:

Using long division:

13x^2 + 13x + 15 <------------Quotient

_________________________

2x^2 - 3x - 5 ) 26x^4 - 13x^3 - 74x^2 - 46x - 24

26x^4 - 39x^3 - 65x^2

26x^3 - 9x^2 - 46x

26x^3 - 39x^2 - 65x

30x^2 + 19x - 24

30x^2 - 45x - 75

64x + 51 <---- Remainder. Division algorithm:

a = bq + r

Here a = the original expression , b = the divisor (2x^2 - 3x - 5), q is the quotient and r = the remainder,

26x^4 - 13x^3 - 74x^2 - 46x - 24 = (2x^2 - 3x - 5)(13x^2 + 13x + 15) + 64x + 51

= 2x^2(13x^2 + 13x + 15) - 3x(13x^2 + 13x + 15) - 5(13x^2 + 13x + 15) + 64x + 51

= 26x^4 + 26x^3 + 30x^2 - 39x^3 - 39x^2 - 45x - 65x^2 - 65x - 75+64x+51

= 25x^4 - 13x^3 - 74x^2 - 46x - 24 which is the same as the above.

User Mpiot
by
5.5k points